Cubic, hexagonal and tetragonal FeGex phases (x = 1, 1.5, 2): Raman spectroscopy and magnetic properties. Issue 37 (14th September 2021) - Kúkoľová, A.; Dimitrievska, M.; Litvinchuk, A. P.; Ramanandan, S. P.; Tappy, N.; Menon, H.; Borg, M.; Grundler, D.; Fontcuberta i Morral, A.
Abstract : Structural properties of various FeGe x compounds are explored by Raman spectroscopy in order to provide reference Raman spectra, and enable fast and local phase determination in FeGe thin films. Abstract : There is currently an emerging drive towards computational materials design and fabrication of predicted novel materials. One of the keys to developing appropriate fabrication methods is determination of the composition and phase. Here we explore the FeGe system and establish reference Raman signatures for the distinction between FeGe hexagonal and cubic structures, as well as FeGe2 and Fe2 Ge3 phases. The experimental results are substantiated by first principles lattice dynamics calculations as well as by complementary structural characterization such as transmission electron microscopy and X-ray diffraction, along with magnetic measurements.